INTEGRATIVE REVIEW ON DIETARY ASSESSMENT INSTRUMENTS IN SCHOOL-AGE CHILDREN - Carla Sílvia Neves da Nova Fernandes; Goreti Filipa Marques; Constança Festas; Fátima Ferreira; Cristiane Silva (Universidade Federal do Paraná, 2017)
Information on a population's dietary intake enables the identification of individuals who are at nutritional risk. The objective of the present study was to identify and analyze existing dietary assessment instruments in school-age children. An integrative review was carried out from 2010 to 2016. For analysis, nine articles were selected according to established inclusion criteria. These enabled the organization of the results into two thematic areas: dietary assessment instruments and limitations in the use of instruments. The most used instrument was the 24-hour dietary recall. The results showed the need for more comprehensive instruments in order to deal with limitations of current instruments in use.